Bibliographic 100 classic graphic design books - Godfrey, Jason (London Laurence King, 2011)
"Covering a huge range of material -- from historic titles by pioneering type foundries to the best of recent monographs from today's leading studios... provides a striking insight into the evolution of graphic design in the twentieth century. Classic graphic design manuals by Laszlo Moholy-Nagy and Josef Muller-Brockmann are included, alongside groundbreaking instructional titles on advertising and corporate identity. Monographs designed by and covering the major individuals and studios of the era -- from A.M. Cassandre and Alexey Brodovitch to Stefan Sagmeister and Peter Saville -- are explored, along with seminal anthologies on trademark design, Polish film posters, the impact of the avant-garde, and more."--book jacket.
Originally published in 2009 (hbk.)
Keywords: Graphic arts -- Bibliography; Graphic arts -- History -- 20th century; Book design